Stress Memory of Recurrent Environmental Challenges in Marine Invasive Species: Ciona robusta as a Case Study - Li, Hanxi; Huang, Xuena; Zhan, Aibin (Frontiers in Physiology, 2020)
Fluctuating environmental changes impose tremendous stresses on sessile organisms in marine ecosystems, in turn, organisms develop complex response mechanisms to keep adaptive homeostasis for survival. Physiological plasticity is one of the primary lines of defense against environmental challenges, and such defense often relies on the antioxidant defense system (ADS). Hence, it is imperative to understand response mechanisms of ADS to fluctuating environments. Invasive species provide excellent models to study how species cope with environmental stresses, as invasive species encounter sudden, and often recurrent, extensive environmental challenges during the whole invasion process. Here, we studied the roles of ADS on rapid response to recurrent cold challenges in a highly invasive tunicate (Ciona robusta) by simulating cold stresses during its invasion process. We assessed antioxidative indicators, including malondialdehyde (MDA), total antioxidant capacity (T-AOC), superoxide dismutase (SOD), catalase (CAT) and glutathione (GSH), as well as transcriptional changes of ADS-related genes to reveal the physiological plasticity under recurring cold stresses. Our results demonstrated that physiological homeostasis relied on the resilience of ADS, which further accordingly tuned antioxidant activity and gene expression to changing environments. The initial cold stress remodeled baselines of ADS to promote the development of stress memory, and subsequent stress memory largely decreased the physiological response to recurrent environmental challenges. All results here suggest that C. robusta could develop stress memory to maintain physiological homeostasis in changing or harsh environments. The results obtained in this study provide new insights into the mechanism of rapid physiological adaption during biological invasions.